Magnesium Oxide Nanoparticles Produced via Biosynthesis Using Pseudomonas aeruginosa, Klebsiella pneumoniae, and Pathogenic Escherichia coli (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The world problem in medicine is multidrug resistance, so all researchers tend to investigate alternative antibacterial materials, for example, nanoparticles. This research aims to synthesize the MgO nanoparticles by using bacteria.  Materials and Methods: survey the ability of some bacteria collected from the Advance Microbial Lab ten isolates (E. coli, Pseudomonas aerogenosa, and Klebsiella pneumoniae). One isolate from each genus of bacteria was chosen for this research, and 10 ml of magnesium nitrate (Mg (NO3)2.6H2O) was added to the culture broth of E.coli at 37ᵒC in a dark shaker water bath. After 24 hours, two molars of sodium-hydroxide solution were added to the chemical reaction mixture to achieve pH 10. The solution color was changed to brown two hours after the addition of the alkaline solution, then MgO NPs were characterization by, ultraviolet -Visible spectrophotometer wave line at (405-630 nm), energy-dispersive x-ray-analysis (EDX) and scanning-electron-microscopy. Results: The result of scanning electron microscopy found the diameters of nano were (31-35,104-109,37.43-40,22) nanometer for E. coli, K. pneumoniae, and P. aeruginosa. The MgO nanoparticle minimum-inhibition concentration detected was 125µg/ml, which affected both G+ and G- bacteria.Conclusion: E. coli, Klebsiella, and Pseudomonas successfully biosynthesized MgO nanoparticles. These nanoparticles exhibited effective antibacterial activity. This suggests that these